1996
DOI: 10.1093/oxfordjournals.aje.a008655
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bone Mineral Density and Sex Hormone Levels with Osteoarthritis of the Hand and Knee in Premenopausal Women

Abstract: Mechanical stress on the cartilage and metabolic and/or hormonal influences have been suggested as possible etiologic factors for osteoarthritis. This paper reports findings from data collected in 1992 that were used to examine associations between osteoarthritis and risk factors in 573 Caucasian women aged 24-45 years from the Michigan Bone Health Study. Radiographs of the dominant hand and both knees were evaluated using the Kellgren and Lawrence grading scale. The prevalence of osteoarthritis (grade 2 or hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 25 publications
2
81
1
4
Order By: Relevance
“…The hip and knee joints have been most studied, with several groups finding evidence of higher systemic BMD in those with OA at these joint sites in a variety of populations. [7][8][9][10][11] Higher BMD has also been reported in association with OA of the spine 10,12 and hand. 9,10,13 A limitation of cross-sectional studies is that the direction of causality cannot be formally assessed.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 94%
“…The hip and knee joints have been most studied, with several groups finding evidence of higher systemic BMD in those with OA at these joint sites in a variety of populations. [7][8][9][10][11] Higher BMD has also been reported in association with OA of the spine 10,12 and hand. 9,10,13 A limitation of cross-sectional studies is that the direction of causality cannot be formally assessed.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 94%
“…Women with low bone density have a higher incidence of fractures, and may be at greater risk of other bony defects which may affect joints. Alternatively, high bone density is associated with osteophytic osteoarthritis, 5,6 and therefore high bone density might be associated with joint symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Data collected from a multidisciplinary hand clinic in London showed that 80% of the patients were women and the majority had developed their symptoms within 4 years of reaching menopause or stopping their menopause hormone therapy (MHT) 3 . This association has also been seen in young women with an early menopause and in those taking aromatase inhibitors after breast cancer 4 . If estrogen does indeed slow OA progression and reduce pain and stiffness, how is this mediated?…”
mentioning
confidence: 72%